An Assessment of the Financial Performance of the Magetan Regency Zakat Institution from the Perspectives of Value for Money and Islamic Accountability - Irfandi (Cakrawala Repositori IMWI)
This study aims to assess the financial performance of zakat institutions in Magetan Regency using the Value for Money approach and Islamic accountability principles. Zakat institutions play a strategic role in collecting, managing, and distributing zakat, infaq, and charitable funds to eligible recipients (mustahik). Therefore, the financial management of zakat institutions is expected to not only comply with administrative requirements but also uphold the principles of economy, efficiency, effectiveness, transparency, trustworthiness, and compliance with Islamic values.This study employs a quantitative descriptive method with a case study approach focusing on the zakat institution in Magetan Regency. The data used consist of financial statements, zakat collection and distribution reports, program documents, and other supporting information related to zakat management accountability. The analysis is conducted using three main Value for Money indicators, namely economy, efficiency, and effectiveness, which are further examined through Islamic accountability principles, including trust (amanah), honesty (siddiq), transparency, equitable distribution, and accountability to Allah SWT and the community.The results of this study are expected to demonstrate the extent to which the zakat institution in Magetan Regency manages public funds optimally, appropriately, and accountably. This research contributes to strengthening the governance of regional zakat institutions by promoting more professional, accountable, and mustahik-oriented management practices.